Effect Maltodextrin on Hedonic Attributes of Tray-Dried Fish Gelatin Powder from Bone of Pangasius sp. - Atma, Yoni; Pakpahan, Josua Wanson (Department of Technology of Agricultural product (THP) Jambi University, 2019)
Abstract—This research aims to drying liquid gelatin from bone of pangasius sp. through maltodexrtrin addition by using tray dehydrator. The stages of this study were including fish bone gelatin extraction and drying of liquid gelatin at 55 oC for 6 hours coupled with addition of maltodextrin (0%, 5%, 8%, 11%, and 14%). The analysis covering gelatin yield and organoleptic parameter i.e hedonic test toward color, aroma, texture, and overall preference. Then, proximate analysis was done also on the selected dried fish bone gelatin. The results shown that maltodextrin addition has significant effect to the hedonic attributes of resulting fish bone gelatin powder by tray drying process. The panelists preference toward fish bone gelatin powder with maltodextrin is like slightly whether to color, aroma, texture, and overall appearance. The yield of dried fish bone gelatin using tray dehydrator is about 16%. The moisture, ash, protein and fat compositions of dried fish bone gelatin in this study were 11.45%, 0.96%, 36.15%, and 0.045% respectively. Keywords—drying; fish gelatin; halal gelatin; maltodextrin; organoleptic